Physico-chemical and mechanical properties of Ti3SiC2-based materials elaborated from SiC/Ti by reactive spark plasma sintering - Faten Turki; Houyem Abderrazak; Frédéric Schoenstein; Florent Têtard; Mohieddine Abdellaoui; Noureddine Jouini (Journal of Advanced Ceramics, 2019)
Abstract In this paper, the synthesis of Ti3SiC2 from SiC/Ti powder using reactive spark plasma sintering (R-SPS) in the temperature range of 1300–1400 °C is reported. The results show that the purity of Ti3SiC2 is improved up to 75 wt% when the holding time is increased from 10 to 20 min at 1400 °C. The thermodynamic and experimental results indicate that Ti3SiC2 formation takes place via the reaction of a pre-formed TiC phase with the silicides, formed from the eutectic compositions. Detailed analysis of mechanical behaviour indicates that samples with higher percentage of secondary phases exhibit higher microhardness and better resistance compared to the near single phase Ti3SiC2.